PENGARUH KUALITAS PRODUK, HARGA, PROMOSI DAN LOKASI TERHADAP KEPUASAN KONSUMEN - Rahmawati, Intan; Andhika, Akbar; Hasanah, Annisa Uswatun; Sanjaya, Vicky F (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2020)
This study aims to examine the effect of product quality, price, promotion and location on customer satisfaction. The method used in this study was a cross-sectional survey design. The sample in this study were consumers of the cafe inspirational corner with a total of 98 respondents. The statistical test was performed using the PLS-based Structural Equation Modeling. The validity test uses the loading factor value, while the reliability test uses the Cronbach'c alpha value, composite reliability and Average Variance Extracted (AVE). After all the results of the indicator items used in this study were valid and reliable, then the hypothesis was tested. Of the four hypotheses proposed, all are supported. The conclusion of this research is the importance of maintaining good product quality, price, promotion and location in order to get customer satisfaction